Tingkat kebugaran dan hubungan antara detak jantung, air tubuh, gejala dehidrasi pada remaja selama pandemi - Mulyawan, Rizki; Prasetyo, Yudik; Arjuna, Fatkurahman; Sumaryanti; Nugroho, Sigit (Universitas Nusantara PGRI Kediri, 2021)
This study was conducted to find out the body response occurred immediately after bleep test after undergoing a pandemic period of more than one year. This research is an analytic observational study with a cross-sectional approach, using the purposive sampling technique. The research subjects were 43 students, 14 women and 29 men with the criteria (1) sports students who were physically active three times a week during the last 1-2 months; (2) no injury or (3) illness in the last 3-7 days. The instruments used are polar heart rate monitor h-10 (measure heart rate), Omron HBF 375 Karada Scan (assess the percentage of water in the body), and urine color scale (dehydration predictor). Data analysis through homogenity test, Kolmogorov-Smirnov normality test, and Pearson Correlation test. The findings of this research were female (30.2 ± 2.63) and male (36.8 ± 5.31) VO2Max concluded as fair category. There was no significant relationship between heart rate with body water (0.071 > 0.05) and urine color (0.557 > 0.05), even body water and urine colour (0.10 > 0.05). The pandemic period is proven to make fitness levels stand in a fair category. Heart rate, body water percentage, and dehydration do not have a significant relationship with each other.